Effective leadership in adventure programming - Priest, Simon PhD; Gass, Michael A. PhD (Champaign, Illinois Human Kinetics, 2018)
In this full-color edition of Effective leadership in Adventure Programming, internationally renowned authors Simon Priest and Michael Gass have significantly updated the content, based on the latest research, issues, and trends in the field of adventure education and leadership. They have reorganized the chapters to conform to their new model of building core competencies. In addition, this third edition includes the following new features: material on technology, social justice, cultural adaptation, sustainability, and facilitation techniques, an online instructor guide that offers activities, discussion questions, and assessments compiled from a group of acclaimed instructors; a digital handbook that offers quick reference to key models, concept, and checklists covered in the text. Effective leadership in adventure programming details both the art and science of adventure leadership, helping a new generation of outdoor leaders develop their skills. The text extends the focus on evidence-based models, theories and best practices, showing that science and research are as important to the profession as the natural beauty of the environment. The book describes the core competencies of outdoor leadership, providing a framework that helps leaders connect with participants in meaningful ways. The focus on the science side is invaluable to new leaders and less-experienced leaders, and it is a great refresher for leaders with more experience. Effective leadership in adventure programming is a valuable resource for the training and education of future outdoor leaders.
1. Evidence -- 2. Philosophy -- 3. Professional ethics -- 4. History -- 5.Technical activity skills -- 6. Safety and risk skills -- 7. Environmental skills -- 8. Organizational skills -- 9. Social Psychology -- 10. Conditional leadership -- 11. Communication -- 12. Instructional skills -- 13. Facilitation skills -- 14. Decision making -- 15. Problem solving -- 16. Sound judgement -- 17. Trends and issues
"This book is a revised edition of Effective Leadership in Adventure Programming, published in 2005 by Human Kinetics"--T.p. verso.
Recommending faculty - Prof. Niño Yabnez
Includes bibliographical references and index
Keywords: Recreation leadership; Recreational therapy; Leisure -- Management; Outdoor recreation -- Management